2020
DOI: 10.1111/are.14493
|View full text |Cite
|
Sign up to set email alerts
|

Thermal challenge of the Indian shrimpPenaeus indicus

Abstract: This study investigated short‐term effects of increasing water temperature from 27 to 41°C on survival and feed consumption of Penaeus indicus at three different ages: PL25 (postlarvae 25 days old), PL50 and PL90. For each age group, water temperature was maintained at 27°C in the control, but increased to 32, 35, 38 and 41°C at a rate of 1°C every eight hours. The temperature was then kept stable until the end of the 7‐day experiment. Results showed that increasing water temperature affected both survival and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Namun demikian, produksi mulai menurun setelah tahun 2006 akibat penyakit dan beralihnya pembudidaya ke udang P. vannamei dan P. monodon (Vance & Rothlisberg, 2020). Sebagai species lokal tentunya lebih adaptif terhadap lingkungan perairan di Indonesia, bahkan dilaporkan tahan terhadap temperature tinggi (Hoang et al, 2020) dan toleransi salinitas yang lebar (Yousif, Kumar, and Ali A 2003;Sajeela et al 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Namun demikian, produksi mulai menurun setelah tahun 2006 akibat penyakit dan beralihnya pembudidaya ke udang P. vannamei dan P. monodon (Vance & Rothlisberg, 2020). Sebagai species lokal tentunya lebih adaptif terhadap lingkungan perairan di Indonesia, bahkan dilaporkan tahan terhadap temperature tinggi (Hoang et al, 2020) dan toleransi salinitas yang lebar (Yousif, Kumar, and Ali A 2003;Sajeela et al 2019).…”
Section: Pendahuluanunclassified
“…Hal ini relevan dengan hasil uji tantang (tanpa aklimatisasi; 96 jam) bahwa larva P. indicus bertahan dengan baik pada salinitas 5-20 ppt (Karan et al, 2020). Namun demikian pemeliharaan larva udang P. indicus di daerah tropis dapat mentoleransi temperatur hingga 35 o C (Hoang et al, 2020). Umumnya pemeliharaan dan produksi benih dilakukan pada suhu >30% dan salinitas >25 ppt, sehingga diperlukan kajian lanjut terhadap kedua parameter tersebut pada level yang lebih rendah.…”
Section: Sintasan Benihunclassified
“…Thus, it is more logical to assess temperature effects on P. helleri via accumulated mortality after a defined period of exposure to the target temperature. This approach has been used for research on penaeid shrimps (Hoang et al., 2020; Hoang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, acute or chronic heat stress can cause a lower reproductive molt rate, embryonic development, and hatching success in Macrobrachium rosenbergii (Mohamad et al 2018). More seriously, heat stress leads to a higher mortality rate in crustaceans, besides the rapid heating rate leads to more deaths (Beladjal et al 2008;Hoang et al 2020). Although speci c thermoreceptors have not been identi ed in crustaceans, studies have found that the peripheral nervous system appears to have maintained thermal sensitivity and adaptation independently of the central nervous system (Lagerspetz and Vainio 2006).…”
Section: Introductionmentioning
confidence: 99%